Sociological Analysis of Factors Affecting the Selection of the Type of Reference Groups among the Citizens of Kermanshah - Azim shakari; Omid aliahmadi; Ali moradi; roshanaei Ali (توسعه اجتماعی, 2022)
The main purpose of this article is a sociological analysis of the factors affecting the selection of the type of reference groups among the citizens of Kermanshah, which was done by survey method and using a questionnaire. The statistical population of this study includes all citizens aged 15 and over in Kermanshah, which according to the 2016 census was equal to 855,523 people. From this population, 570 people were selected based on Cochran's formula and selected using cluster random sampling. Statistical analyzes were performed using SPSS and AMOS software. Findings show that the level of education (r =0.143), tendency to modernity (r =0.164), religiosity (r =0.351) and the use of mass media (r =0.261) by selecting the type Reference groups had a significant relationship, but migration and exposure or non-exposure to war did not affect the choice of type of reference groups. The results of regression analysis also show that the variable of religiosity could explain 0.28 of the changes related to the selection of the type of reference groups.